An Innovative Application of a Solar Storage Wall Combined with the Low-Temperature Organic Rankine Cycle. (7th September 2014) - Hung, Tzu-Chen; Lee, Duen-Sheng; Lin, Jaw-Ren
Abstract : The objective of this study is to collect energy on the waste heat from air produced by solar ventilation systems. This heat used for electricity generation by an organic Rankine cycle (ORC) system was implemented. The advantages of this method include the use of existing building's wall, and it also provides the region of energy scarcity for reference. This is also an innovative method, and the results will contribute to the efforts made toward improving the design of solar ventilation in the field of solar thermal engineering. In addition, ORC system would help generate electricity and build a low-carbon building. This study considered several critical parameters such as length of the airflow channel, intensity of solar radiation, pattern of the absorber plate, stagnant air layer, and operating conditions. The simulation results show that the highest outlet temperature and heat collecting efficiency of solar ventilation system are about 120°C and 60%, respectively. The measured ORC efficiency of the system was 6.2%. The proposed method is feasible for the waste heat from air produced by ventilation systems.